Functionalized nanoparticles to deliver nucleic acids to the brain for the treatment of Alzheimer’s disease - Muolokwu, Chinenye Edith; Chaulagain, Bivek; Gothwal, Avinash; Mahanta, Arun Kumar; Tagoe, Benjamin; Lamsal, Babita; Singh, Jagdish (Frontiers in Pharmacology, 2024)
Brain-targeted gene delivery across the blood-brain barrier (BBB) is a significant challenge in the 21st century for the healthcare sector, particularly in developing an effective treatment strategy against Alzheimer’s disease (AD). The Internal architecture of the brain capillary endothelium restricts bio-actives entry into the brain. Additionally, therapy with nucleic acids faces challenges like vulnerability to degradation by nucleases and potential immune responses. Functionalized nanocarrier-based gene delivery approaches have resulted in safe and effective platforms. These nanoparticles (NPs) have demonstrated efficacy in protecting nucleic acids from degradation, enhancing transport across the BBB, increasing bioavailability, prolonging circulation time, and regulating gene expression of key proteins involved in AD pathology. We provided a detailed review of several nanocarriers and targeting ligands such as cell-penetrating peptides (CPPs), endogenous proteins, and antibodies. The utilization of functionalized NPs extends beyond a singular system, serving as a versatile platform for customization in related neurodegenerative diseases. Only a few numbers of bioactive regimens can go through the BBB. Thus, exploring functionalized NPs for brain-targeted gene delivery is of utmost necessity. Currently, genes are considered high therapeutic potential molecules for altering any disease-causing gene. Through surface modification, nanoparticulate systems can be tailored to address various diseases by replacing the target-specific molecule on their surface. This review article presents several nanoparticulate delivery systems, such as lipid NPs, polymeric micelles, exosomes, and polymeric NPs, for nucleic acids delivery to the brain and the functionalization strategies explored in AD research.